2001
DOI: 10.1159/000045991
|View full text |Cite
|
Sign up to set email alerts
|

The Polymorphonuclear Leukocyte – A New Target for Erythropoietin

Abstract: A previous study from our laboratory has shown that erythropoietin (EPO), beside its traditional role in erythropoiesis, acts as an alleviator of oxidative stress and inflammation in chronic hemodialysis (HD) patients, conferred in part by activated polymorphonuclear leukocytes (PMNLs). To substantiate this phenomenon, the existence of EPO receptors (EPO-Rs) on PMNL membrane was examined at the transcriptional and translational levels. mRNA for EPO-R was detected in PMNLs using specific primers directed toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…The detection of EPO-Rs in cells other than erythroid progenitors, such as polymorphonuclear leukocytes, megakaryocytes, endothelial, myocardial and neural cells (Anagnostou et al, 1994;Brines and Cerami, 2005;Buemi et al, 2003;Fraser et al, 1989;Jaquet et al, 2002;Sela et al, 2001) showed that besides its role in erythropoiesis, EPO has additional biological functions. It should be noted that alongside the beneficial effects of EPO, a concern that EPO treatment for anemia might adversely affect the prognosis in certain cases of solid tumor cancers (Aapro et al, 2008;Henke et al, 2006;Longmore, 2007) has been raised.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of EPO-Rs in cells other than erythroid progenitors, such as polymorphonuclear leukocytes, megakaryocytes, endothelial, myocardial and neural cells (Anagnostou et al, 1994;Brines and Cerami, 2005;Buemi et al, 2003;Fraser et al, 1989;Jaquet et al, 2002;Sela et al, 2001) showed that besides its role in erythropoiesis, EPO has additional biological functions. It should be noted that alongside the beneficial effects of EPO, a concern that EPO treatment for anemia might adversely affect the prognosis in certain cases of solid tumor cancers (Aapro et al, 2008;Henke et al, 2006;Longmore, 2007) has been raised.…”
Section: Introductionmentioning
confidence: 99%
“…Cloning of the Epo gene has led to the introduction of recombinant human Epo (rHuEpo) into clinical practice as a treatment for various anemias, including anemia related to chronic kidney disease and certain forms of cancer [1, 2]. Detection of the target receptor for Epo (EpoR) in cells other than erythroid progenitors, such as polymorphonuclear leukocytes, megakaryocytes, endothelial, myocardial and neural cells [3][4][5][6][7], suggests that Epo has other biological functions beyond erythropoiesis, and may have further potential therapeutic applications. These effects include improvement in congestive heart failure [8,9] and neuroprotection [10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…The upregulation of ICAM-1 in tg6 mice emphasizes this point and could also help explain the previous negative outcome observed in these mice after MCAO. In the absence of injury, however, because leukocytes express functional Epo receptors (38), Epo may directly interact with and reduce the number of leukocytes and slow the inflammatory response as a whole (39). Although a detrimental effect of high Epo levels on the vasculature cannot be ruled out, clinically Epo is a very well studied and frequently used compound, and all current evidence suggests that this is unlikely to be the case (for a review see Ref.…”
Section: Discussionmentioning
confidence: 99%